Pemanfaatan Media Digital untuk Pendidikan Toleransi di Sekolah Dasar - Nurjannah, Mawar Datul; Bella, Ikfi Istiana; Salsabila, Nabila; Nisa, Muflihatun; Fitriyah, Eliyatul (TARBAWIYAT, 2025)
This study analyzes the utilization of digital media as a supporting instrument for tolerance education in elementary schools based on a systematic review of relevant literature. The research aims to identify the forms of digital media commonly used, examine how these media support the internalization of tolerance values, and explore the challenges affecting their effectiveness in the learning process. Using a library research approach, data were collected from books, journal articles, proceedings, and research reports focusing on digital literacy, character education, and tolerance development. The findings indicate that digital media such as educational videos, animations, interactive applications, and digital learning platforms play an important role in enhancing student engagement and helping children understand tolerance through multisensory, contextual, and concrete representations. However, variations in effectiveness were found due to differences in teachers’ digital literacy skills, content design quality, technological access, and students’ characteristics. The study also highlights challenges related to content neutrality, contextual relevance, infrastructure limitations, and pedagogical implementation. Despite these obstacles, digital media remain highly promising for strengthening tolerance values when properly designed and integrated into reflective learning activities. These findings demonstrate the strategic role of technology in character education and emphasize the need for adaptive content development, equitable access, and continuous evaluation.